Analisis Kelayakan Investasi Pada Saham Perusahaan Manufaktur Sub Sektor Food And Bavarages Di Bursa Efek Indonesia (BEI) Pada Tahub 2019-2022 - Wungu Muharomi; Nani Septiana; Karnila Ali; Faiz Dwi Nugroho (Universitas Muhammadiyah Metro, 2025)
Investors who invest in the capital market will find two problems, namely the rate of returnand the level of risk. The purpose of this study was to determine the eligibility level of sharesand the rate of return on shares and risk by using the CAPM method in determininginvestment decisions in shares of manufacturing companies in the Food and Beverages sub-sector which are listed on the Indonesia Stock Exchange (IDX) in 2019-2022. This study usesa descriptive quantitative approach to identify the feasibility of shares based on the level andreturn on investment. The sample in this study are food and beverage manufacturingcompanies listed on the IDX for 2019-2022. Data collection techniques using thedocumentation method and data analysis using the CAPM method. Based on the results of thefeasibility research on stock investment that has been carried out, in this study there werefour stocks that were declared eligible for the stock investment activities, namely ADES,CEKA, MYOR, and STTP. Meanwhile, six companies namely ALTO, ICBP, INDF, ROTI,SKBM, and ULTJ were declared unfit for investment activities. Individual stock returns (Ri)in companies from highest to lowest are ADES, STTP, MYOR, and CEKA. While thesystematic risk (β) from highest to lowest is ADES, CEKA, MYORand STTP